Constructing authentication web in cloud computing. Issue 15 (13th February 2015) - Zhao, Gansen; Ba, Zhongjie; Wang, Xinming; Zhang, Feng; Huang, Changqin; Tang, Yong
Abstract: Cloud computing offers a cheap and efficient solution for the deployment of web applications. It results in a big increase of the number of service provider. Users hold multiple identities for using services from different domains. The openness of public clouds requires the authentication system to accept user identities from various domains and to support hybrid authentication protocols. This work proposes a cross‐domain single sign‐on mechanism to address the preceding issues and makes a formal mathematical model to analyze the security issues of the proposed mechanism's authentication architecture; furthermore, an algorithm is proposed to detect the authentication architecture's weak vertex whose failure would lead to a partial failure in the architecture. The proposed mechanism allows service providers to verify user identities in a decentralized way and allows users to unify their identities from various domains in a safe way. The verification process used in this mechanism is able to support hybrid authentication protocols as well as to accelerate the verification of credentials by eliminating single point of failure and single‐point bottleneck. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : This work proposes a cross‐domain single sign‐on mechanism. It allows service providers to verify user identities in a decentralized way and allows users to unify their identities from various domains in a safe way. The verification process used in this mechanism is able to support hybrid authentication protocols as well as to accelerate the verification of credentials by eliminating single point of failure and single‐point bottleneck.